Rambutan seed germination: Temperature and storage - De Andrade, Renata Aparecida [UNESP]; Bagatim, Amanda Garcia [UNESP]; Nacata, Guilherme [UNESP] (My University, 2017)
The objective of this study was to verify if the germination temperature, storage condition and period could influence rambutan seeds germination. The research were realized in two stages, corresponding to rambutan seeds storage management: after extracted from the fruits or kept in the fruits, until sowing. Storage condition were also evaluated: low temperature (10oC) and room temperature, being realized the sowing at 0 (control), 3, 6, 9 and 12 days after storage, at different germination temperatures: 20, 25, 30, 35 and 40°C. The seeds were placed in plastic containers with commercial substrate with pine, using four repetitions with 10 seeds for each. The percentage and period of germination were assessed. The experimental design was completely randomized and the data was evaluated by variance analysis, applying Tukey´s test at 5% of significance for means with significant difference. According to the results, it is possible to conclude that the best temperature for rambutan germination is 25°C and the storage can be realized with the seeds inside the fruit until the time of sowing, in up tol six days.
Keywords: Nephelium lappaceum L; Propagation; Seedling obtaining; Storage